Increased efficiency of Campylobacter jejuni N-oligosaccharyltransferase PglB by structure-guided engineering. Issue 4 (April 2015) - Ihssen, Julian; Haas, Jürgen; Kowarik, Michael; Wiesli, Luzia; Wacker, Michael; Schwede, Torsten; Thöny-Meyer, Linda
Abstract : Conjugate vaccines belong to the most efficient preventive measures against life-threatening bacterial infections. Functional expression of N -oligosaccharyltransferase ( N -OST) PglB of Campylobacter jejuni in Escherichia coli enables a simplified production of glycoconjugate vaccines in prokaryotic cells. Polysaccharide antigens of pathogenic bacteria can be covalently coupled to immunogenic acceptor proteins bearing engineered glycosylation sites. Transfer efficiency of PglB Cj is low for certain heterologous polysaccharide substrates. In this study, we increased glycosylation rates for Salmonella enterica sv. Typhimurium LT2 O antigen (which lacks N -acetyl sugars) and Staphylococcus aureus CP5 polysaccharides by structure-guided engineering of PglB. A three-dimensional homology model of membrane-associated PglB Cj, docked to the natural C. jejuni N -glycan attached to the acceptor peptide, was used to identify potential sugar-interacting residues as targets for mutagenesis. Saturation mutagenesis of an active site residue yielded the enhancing mutation N311V, which facilitated fivefold to 11-fold increased in vivo glycosylation rates as determined by glycoprotein-specific ELISA. Further rounds of in vitro evolution led to a triple mutant S80R-Q287P-N311V enabling a yield improvement of S. enterica LT2 glycoconjugates by a factor of 16. Our results demonstrate that bacterial N -OST can be tailored to specific polysaccharide substrates by structure-guided protein engineering.